Paediatric familial hypercholesterolaemia screening in Europe: public policy background and recommendations - Gidding, Samuel S; Wiegman, Albert; Groselj, Urh; Freiberger, Tomas; Peretti, Noel; Dharmayat, Kanika I; Daccord, Magdalena; Bedlington, Nicola; Sikonja, Jaka; Ray, Kausik K; Santos, Raul D; Halle, Martin; et al. (European journal of preventive cardiology, 2022)
Familial hypercholesterolaemia (FH) is under-recognized and under-treated in Europe leading to significantly higher risk for premature heart disease in those affected. As treatment beginning early in life is highly effective in preventing heart disease and cost-effective in these patients, screening for FH is crucial. It has therefore now been recognized by the European Commission Public Health Best Practice Portal as an effective strategy. Model programmes exist in Europe to identify young individuals with FH, which are based on cascade screening of first-degree relatives of affected individuals, universal screening for high cholesterol, opportunistic screening of high-risk individuals, or a combination of the above approaches. Recommendations presented herein to improve identification of FH emphasize that every country should have an FH screening programme. These programmes should be adapted from existing strategies to best fit the individual country's healthcare system, governments should provide financial support for these programmes and related care, and further research to optimize care and implementations should be conducted.
Keywords: Cholesterol; hyperlipoproteinemie typ II; Cholesterol, LDL; Humans; dítě; nemoci srdce; Child; LDL cholesterol; Preventive cardiology; rizikové faktory; lidé; Europe; Hyperlipoproteinemia Type II; LDL-cholesterol; Familial hypercholesterolaemia; Public Policy; Myocardial infarction; Mass Screening; veřejná politika; genetické testování; plošný screening; Genetic Testing; Evropa; Risk Factors; Heart Diseases